First principles calculations of the electronic properties of O- and O2-NbSe2 complexes - Pido, Alvanh Alem G.; Pagcaliwagan, Bryan P. (International Journal of Computing Sciences Research; Vol 6 (2022): Vol 6, 2022)
Purpose – We investigated the interaction of O and O 2 on monolayer Niobium Diselenide (NbSe 2 ) to provide theoretical predictions about the electronic properties of the complexes using First principles calculations in Quantum Espresso 6.7. As known, considering impurities in pristine nanomaterials like NbSe 2 is very important as it can alter some of its properties. Method – In this paper, we performed some topological analyses on the electronic densities and electronic structures calculations to O- and O 2 -NbSe 2 complexes. Charge Density Difference (CDD) and Bader charge analysis reveal that O and O 2 acted as oxidizing agents and accumulated electronic charges from the NbSe 2 . Results – The electronic properties calculations of the complexes showed that the metallic behavior of NbSe 2 is preserved after O and O 2 adsorption. Calculations of the net charge transfer revealed that the atomic and molecular oxygen has accumulated electronic charges while the NbSe 2 has depleted electronic charges. These results showed the possibility of tailoring the electronic properties of NbSe 2 . Conclusion – The interaction of O and O 2 with the monolayer NbSe 2 caused charge redistributions while maintaining the metallicity of the NbSe 2 . In all circumstances, the results are consistent with the established works which show the possibility of modifying the electronic properties of NbSe 2 that could open some potential applications in nanotechnology and other nanoelectronics-related devices. Recommendation – Further calculations could be done like electron localization function, optical properties, and vibrational properties, to understand more the nature of their interaction. Practical Implication – This study provided insights and theoretical predictions on the electronic properties of oxygen adsorption to NbSe 2 which could help to better understand how metallic nanomaterials like NbSe 2 react with oxygen, leading to some potential applications.